Live Imaging of Phosphate Levels in Arabidopsis Root Cells Expressing a FRET-Based Phosphate Sensor - Assunção, Ana G. L.; Gjetting, Sisse K.; Hansen, Michael; Fuglsang, Anja T.; Schulz, Alexander (Plants (Basel), 2020)
Phosphorous (P) is an essential macronutrient in all organisms serving various fundamental biological processes, and is one of the least available plant nutrients in the soil. The application of inorganic phosphate (Pi) fertilizers is frequent, but it has a high environmental and financial cost. Breeding crops for improved Pi use-efficiency is a promising plant-based solution to pursue a reduction of fertilizer dependency. Availability of tools for monitoring changes of plant cellular Pi concentration in real-time can contribute to advancing knowledge on the molecular basis of Pi transport and homeostasis in plants. Genetically encoded fluorescent sensors have provided new insight on cellular processes. Here, we show that two Pi Fluorescence Resonance Energy Transfer (FRET)-based sensors from the FLIPPi family, the low-affinity FLIPPi-30m and the high-affinity FLIPPi-4µ, can be expressed and analyzed in Arabidopsis thaliana with wild-type background. These FLIPPi sensors had not been tested in plants, but only in mammalian cell lines. We show FRET response and live imaging of Pi levels in seedling roots of Arabidopsis FLIPPi-30m and FLIPPi-4µ lines. Our results reinforce that sensors from the FLIPPi family are valuable tools for studying mechanisms of Pi transport and homeostasis in plants, and for research towards a more sustainable use of Pi fertilization.